The effect of COVID certificates on vaccine uptake, health outcomes and the economy - Miquel Oliu-Barton; Bary B. S. R. Pradelski; Nicolas Woloszko; Lionel Guetta-Jeanrenaud; Philippe Aghion; Patrick Artus; Arnaud Fontanet; Philippe J. Martin; Guntram B. Wolff (Bruegel, 2022)
In the COVID-19 pandemic, governments have, among other measures, mandated the use of COVID certificates to prove vaccination, recovery or a recent negative test, and have required individuals to show certificates to access shops, restaurants, and education or workplaces. While arguments for and against COVID certificates have focused on reducing transmission and ethical concerns, the incentive effects of COVID certificates on vaccine uptake, health outcomes and the economy has not yet been investigated. To estimate these effects, we construct counterfactuals based on innovation diffusion theory for France, Germany and Italy. We estimate that the announcement of COVID certificates during summer 2021 led to increased vaccine uptake in France of 13.0 (95% CI 9.7-14.9) percentage points (p.p.) of the total population up to the end of the year, in Germany 6.2 (2.6-6.9) p.p., and in Italy 9.7 (5.4-12.3) p.p. Further, this averted an additional 3,979 (3,453-4,298) deaths in France, 1,133 (-312-1,358) in Germany, and 1,331 (502-1,794) in Italy; and prevented gross domestic product (GDP) losses of exteuro6.0 (5.9-6.1) billion in France, exteuro1.4 (1.3-1.5) billion in Germany, and exteuro2.1 (2.0-2.2) billion in Italy. Notably, the application of COVID certificates substantially reduced the pressure on intensive care units (ICUs) and, in France, prevented occupancy levels being exceeded where prior lockdowns were instated. Varying government communication efforts and restrictions associated with COVID certificates may explain country differences, such as the smaller effect in Germany. Overall, our findings are more sizeable than predicted. This analysis may help inform decisions about when and how to employ COVID certificates to increase vaccine uptake and thus avoid stringent interventions, such as closures, curfews, and lockdowns, with major social and economic consequences.
Keywords: 330; COVID-19; health economics and policy